Model Pemilihan Rute Antara Jalan Nasional dan Jalan Tol Surabaya (Bundaran Waru)-Jombang dengan Metode Pembebanan Bertahap - Pratama, Irsyadul Ibad; Sholichin, Ibnu; Utomo, Nugroho (Universitas Batanghari Jambi, 2024)
The interactions that occur between the City of Surabaya and the City of Jombang are not only influenced by economic factors, but are also influenced by social factors of life. Residents who are outside the Jombang City area will try to choose the fastest route from several routes that connect their home zone with Jombang City. This research was conducted based on factors that influence the process of choosing a travel route from Surabaya City to Jombang City using class I, class II and class III vehicles. The influencing factors are travel time and vehicle flow. The available route options are via national roads and toll roads. In this research, an analysis of route selection was carried out using the gradual loading method. The gradual loading method was chosen because it can determine the relationship between traffic flow and travel time, without depending on driver assumptions and road network characteristics. After carrying out the analysis using the gradual loading method, the wardrop balance value can then be calculated, the results of which can show that the conditions are balanced and the driver can determine which route to take. From the results of a simple linear regression analysis, a model of the flow - travel cost relationship on the Surabaya - Jombang National Road route was obtained with the equation form 55.63 + 0.031X, while on the Surabaya - Jombang Toll Road route the equation form was 32.044 + 0.024X. The wardrop balance value at a uniform fraction loading of 25% was found to be 0.18 and at a uniform fraction loading of 10% and a non-uniform fraction of 10%, 20%, 30%, 40% the value was 0.03. This value is relatively small and can be interpreted that the condition is close to wardrop equilibrium.